CONTRIBUTION A UNE ETUDE MORPHO-HISTOMETRIQUE DE CISTUS LADANIFERUS SUBSP. AFRICANUS DANS LA REGION DE TLEMCEN (ALGERIE OCCIDENTALE) - Henaoui, Smain El-Amine; Bouazza, Mohammed (European Scientific Journal, ESJ, 2013)
Tlemcen region is characterized by an integral part of several environmental constraints that may affect the morphology of the species Mediterranean ecosystems. This has led us to a biometric study of Cistus ladaniferus subsp. africanus, to demonstrate the adaptation of this species in his biotope. This work will also allow us to understand the morphology of Cistus ladaniferus subsp. africanus and its ecological significance. It is obvious that the species lives in a particular environment where it has environmental requirements in order to grow normally. Histological sections allowed us to describe the different tissues of the species and their arrangement in the stem and root. The histometry remains an essential way to see the size of each tissue at the two organs studied in order to understand the relationship and the influence of one on the other. Finally, the statistical study, using correlations, we were able to interpret the various morphological and histological measurements.